2010
DOI: 10.1063/1.3358249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing on the magnetic tunnel junction with Co/Pt perpendicular anisotropy ferromagnetic multilayers

Abstract: Perpendicular magnetic tunnel junctions (pMTJs) with tunneling magnetoresistance (TMR) as high as 14.7% at room temperature were fabricated. The continuous film and pMTJs with Co/Pt multilayer magnetic electrodes and AlOx tunnel barrier were annealed at different temperatures and the effect of annealing on their properties was investigated. The hysteresis loops and X-ray reflectivity measurement show that the interdiffusion of Co and Pt atoms is slight when annealed below 523 K. However, the patterned magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Promising materials with perpendicular magnetic anisotropy are Co based multilayers, such as Co/Pd or Co/Pt [14]. These materials have been successfully integrated into MTJs [15][16][17][18][19][20]. In this study, temperature-and bias voltage-dependent transport measurements of MgO-based pMTJs with Co/Pd multilayers as electrodes are presented and compared to measurements of MTJs with Co 40 Fe 40 B 20 electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Promising materials with perpendicular magnetic anisotropy are Co based multilayers, such as Co/Pd or Co/Pt [14]. These materials have been successfully integrated into MTJs [15][16][17][18][19][20]. In this study, temperature-and bias voltage-dependent transport measurements of MgO-based pMTJs with Co/Pd multilayers as electrodes are presented and compared to measurements of MTJs with Co 40 Fe 40 B 20 electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…4(b) shows that more than 4dB SNR gain is obtained with a large ac field vertical amplitude (Hy~0.15Hc) with a 6nm FGL, and this model shows larger SNR gain than the model with 3nm FGL at the same Hy. In high anisotropy media, the horizontal component of ac field is the key for SNR gain in MAMR [11], since bit switching happens near the edge of main pole and farther away from the FGL (compare to the recording in low anisotropy media), and the vertical ac field decreases more than the horizontal ac field. When the rise time following a function of…”
Section: Resultsmentioning
confidence: 99%
“…Multilayers should be used in real MAMR system, but the recording on a monolayer medium is the basic model to evaluate the influence of STO ac field on MAMR in the CoX/Pt media with different magnetic properties. Many experimental papers [11,13] showed that n has to be much larger than 1 to obtain large perpendicular anisotropy and enough thermal stability in (CoX/Pt)n multilayer films. Our former simulation [12], however, has proved that the coercivity does not change when the n in (CoX/Pt)n increase from 1 to 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The main limitation of using CoFeB is the thinness of the electrodes (<1.6 nm) which is necessary for PMA, as at this thickness thermal stability can be an issue. 7 Rare-earth/transition metal ferrimagnet alloys, 8 [Fe 1-x Co x /Pt] multilayers (MLs), 9,10 and L1 0 (Fe,Co)Pt alloys 11 have also been tested since they have large PMA. However, both these systems have large damping and low spin polarization.…”
mentioning
confidence: 99%